Design and simulation of solar roof-top projects for an energy self-reliant university campus - Ajith, Gopi; K., Sudhakar; Ngui, Wai Keng (IOP Publishing, 2021)
A University campus becoming self-reliant in terms of electricity generation is always important. The power requirement of a University campus is mainly for its academic blocks for different departments. The laboratories, libraries, and hostel facilities also require continuous power needs. Conventionally, the electricity needs are met utilizing the power received from the local utility and the University will be paying for it based on the tariff fixed by the local regulators and agreed by the utility. It is proposed to install Solar Roof-top PV power plants in shade-free rooftops of the buildings inside a University campus to offset the University’s electricity needs and to make the University self-reliant in terms of electricity generation and consumption. This integrated and comprehensive solar project is intended to reduce the carbon footprint of the University and aiming for a carbon-neutral campus. Detailed feasibility studies have been conducted for installing solar roof-top power plants in the selected building roof-tops of the University. Based on the feasibility study, design and simulation have been carried out for a total 1.6MWp capacity of solar roof-top projects to completely offset the total electricity needs of the University based on the current electricity consumption patterns. The design and simulation are accomplished utilizing PVsyst software and the economic and environmental analysis has been carried out utilizing RETscreen software for arriving at the results